(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
As a result of the theoretical analysis of the fact that the graphic organizer used in education is a "visual educational tool" through examples of pedagogical, psychological and philosophical literature, clarifying the concept of "graphic organizer" and clarifying that it is an educational tool, As a result of students’ creation of graphic organizer "models" such as "Hierarchy diagram", "Mind map", "FSMU", "Multiple meaning", "Fish skeleton" through the software "MindOnMap" , the development of skills and competences, consideration of the advantages of use from the point of view of the effectiveness of language education.